Pengaruh Unggahan Pada Media Sosial Instagram @Prabowo Terhadap Citra Politik Prabowo Subianto - Aprine, Nurisgiah Dwi; Tayo, Yanti; Ramdhani, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
The motivation for this study stemmed from the frequent posts on the Instagram social media account @prabowo, which has become a popular subject of discussion among individuals in Indonesia. The objective is to determine the extent to which posts on the Instagram account @prabowo impact Prabowo Subianto's political image. This study employs quantitative methodologies, namely an explanatory survey. The study use the Image Formation Theory as its main theoretical framework, supplemented by the media exposure theory. The research population consisted of individuals who followed the Instagram account @prabowo. The sample was selected using a Non-Probability Sampling approach, namely the purposive sampling method. The data gathering method used was a survey conducted via the use of Google Form. Additionally, the data analysis approach employs a Likert scale. The findings of this study demonstrated that the frequency, substance, and level of attention in posts on the social media platform Instagram, namely the account @prabowo, had a substantial impact on the political image of Prabowo Subianto.